Evaluation of the clinical effectiveness of a modified technique of injecting PRP-therapy in complex treatment of generalized periodontitis patients with concomitant cardiovascular diseases - Kopchak, O. V. (Journal of Education, Health and Sport, 2017)
The results of the study made show high therapeutic efficacy in the treatment of generalized periodontitis with concomitant cardiovascular diseases in the application of plasma enriched with platelets obtained by the method modified by the authors.